2013
DOI: 10.1371/journal.pone.0070713
|View full text |Cite
|
Sign up to set email alerts
|

Do Price Subsidies on Artemisinin Combination Therapy for Malaria Increase Household Use?: Evidence from a Repeated Cross-Sectional Study in Remote Regions of Tanzania

Abstract: BackgroundThe Affordable Medicines Facility-malaria (AMFm) is a pilot program that uses price subsidies to increase access to Artemisinin Combination Therapies (ACTs), currently the most effective malaria treatment. Recent evidence suggests that availability and affordability of ACTs in retail sector drug shops (where many people treat malaria) has increased under the AMFm, but it is unclear whether household level ACT use has increased.Methods and FindingsHousehold surveys were conducted in two remote regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Several trials across Africa have found that subsidies on RDTs and ACTs substantially increase their purchase and appropriate use for antimalaria treatment in retail shops. [35][36][37][38][39][40] If age-related differences are more attributable to perceptions of malaria risks, informational campaigns would be needed to encourage the use of recommended care. This study did not disentangle the reasons for different treatment-seeking choices.…”
Section: Discussionmentioning
confidence: 99%
“…Several trials across Africa have found that subsidies on RDTs and ACTs substantially increase their purchase and appropriate use for antimalaria treatment in retail shops. [35][36][37][38][39][40] If age-related differences are more attributable to perceptions of malaria risks, informational campaigns would be needed to encourage the use of recommended care. This study did not disentangle the reasons for different treatment-seeking choices.…”
Section: Discussionmentioning
confidence: 99%
“…It is not able directly to examine the final one, to increase ACT use, and there is evidence that in some settings increasing availability of affordable ACTs in the private sector does not in itself necessarily increase use, although in others it has been found to. 21,22 …”
Section: Discussionmentioning
confidence: 99%
“…ADDOs are allowed to sell a limited number of prescription-only drugs, including an approved list of antibiotics and anti-malarial drugs. Availability of ACT was limited in ADDOs until the implementation of the Affordable Medicines Facility- malaria (AMFm) in 2010, which led to a significant reduction in price and a corresponding increase in availability [ 23 , 27 ].…”
Section: Introductionmentioning
confidence: 99%